2001
DOI: 10.1074/jbc.c000833200
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Jellyfish Green Fluorescent Protein via the Tat System of Escherichia coli and Change of Its Periplasmic Localization in Response to Osmotic Up-shock

Abstract: The bacterial twin arginine translocation (Tat) pathway is capable of exporting cofactor-containing enzymes into the periplasm. To assess the capacity of the Tat pathway to export heterologous proteins and to gain information about the property of the periplasm, we fused the twin arginine signal peptide of the trimethylamine N-oxide reductase to the jellyfish green fluorescent protein (GFP). Unlike the Sec pathway, the Tat system successfully exported correctly folded GFP into the periplasm of Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
121
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 34 publications
18
121
0
Order By: Relevance
“…35). Interestingly, c-myc-HybC was notably absent from both the cytoplasmic and periplasmic fractions of ⌬tatC cells, consistent with reports that some nonexported Tat substrates are efficiently degraded by an unidentified ''housecleaning'' mechanism (30,36). Importantly, these results confirm that hitchhiker export can be functionally reconstituted using multicopy expression plasmids.…”
supporting
confidence: 76%
“…35). Interestingly, c-myc-HybC was notably absent from both the cytoplasmic and periplasmic fractions of ⌬tatC cells, consistent with reports that some nonexported Tat substrates are efficiently degraded by an unidentified ''housecleaning'' mechanism (30,36). Importantly, these results confirm that hitchhiker export can be functionally reconstituted using multicopy expression plasmids.…”
supporting
confidence: 76%
“…In a strain expressing TorAss-YFP, most cells showed bright, uniform fluorescence, but some cells (about 10%) exhibited the same fluorescent haloes as those described in previous studies ( Fig. 7A4) (Santini et al, 2001;Thomas et al, 2001). We attributed the uniform fluorescence to overproduction of the fusion protein and inefficient export by the Tat system.…”
Section: Fusion Of Mmpa To Mrfp1 -An Effective Periplasmic Fluorescesupporting
confidence: 48%
“…In the FA113 tatC::spec strain, no F AB could be detected in the periplasmic fraction and a significant reduction in the amount of protein remaining in the cytoplasm was also observed. We and others have observed that depletion of the tat genes often results in inactivation or degradation of Tat substrate proteins in the cytoplasm (32,33). Similarly, no light-chain protein or F AB -binding activity could be detected in E. coli DHB4 (Fig.…”
Section: Alkaline Phosphatase Can Be Exported By Tat Only In Strains mentioning
confidence: 99%